Examining University Students’ Motivation in A Virtual Academic Mobility Program: A Malaysian Case - Khairunesa ISA; Sarala Thulasi PALPANADAN; Nurliyana MD ROSNI (Communications of International Proceedings, 2022)
The spread of Covid-19 pandemic has affected changes in human’s daily routines. The implementation of new norms has emphasized many aspects including social distancing, avoiding crowded areas and taking care of personal hygiene. This has affected the implementation of academic mobility programme which is currently conducted via physical and face to face approach where, the academic mobility program should be conducted virtually. This study attempted to determine the student motivation level to join the virtual mobility and identify the factors that motivated students to join virtual mobility programs. In addition, this study also investigated the possibilities of having differences in student motivation factor based on gender. A total of 350 Malaysian university students were involved as respondents in this study. The findings showed that student motivation level to join the virtual academic mobility was at the moderate level and there was a significant difference between the motivation level of male and female students in joining the virtual academic mobility programme.
Keywords: higher education; new norms; Information Communication Technology and virtual mobility; gender-based differences